The influence of English on lexical borrowing in the Kelantan Malay dialect / Wan Afiqah Anis Wan Ahmad - Wan Ahmad, Wan Afiqah Anis (2019)
The main aim of this research is to investigate the lexical borrowing of the Kelantan Malay dialect that have been influenced by the English language. The objectives of the study were to identify the Kelantan Malay words that have been borrowed from the English language and to examine the phonological changes that those words have undergone.